Vitamin D and IFN-β Modulate the Inflammatory Gene Expression Program of Primary Human T Lymphocytes - Bianchi, Niccolò; Emming, Stefan; Zecca, Chiara; Monticelli, Silvia (Frontiers in Immunology, 2020)
IFN-beta treatment is a commonly used therapy for relapsing-remitting multiple sclerosis (MS), while vitamin D deficiency correlates with an increased risk of MS and/ or its activity. MS is a demyelinating chronic inflammatory disease of the central nervous system, in which activated T lymphocytes play a major role, and may represent direct targets of IFN-beta and vitamin D activities. However, the underlying mechanism of action of vitamin D and IFN-, alone or in combination, remains incompletely understood, especially when considering their direct effects on the ability of T lymphocytes to produce inflammatory cytokines. We profiled the expression of immune-related genes and microRNAs in primary human T lymphocytes in response to vitamin D and IFN-beta, and we dissected the impact of these treatments on cytokine production and T cell proliferation. We found that the treatments influenced primarily memory T cell plasticity, rather than polarization towards a stable phenotype. Moreover, our data revealed extensive reprogramming of the transcriptional output of primary T cells in response to vitamin D and IFN-beta and provide the bases for further mechanistic insights into these commonly used treatments.